Inhibition of crossed-beam energy transfer induced by expansion-velocity fluctuations. (15th February 2018) - Neuville, C; Glize, K; Loiseau, P; Masson-Laborde, P-E; Debayle, A; Casanova, M; Baccou, C; Labaune, C; Depierreux, S
Abstract: Crossed-beam energy transfer between three laser beams has been experimentally investigated in a flowing plasma. Time-evolution measurements of the amplification of a first beam by a second beam highlighted the inhibition of energy transfer by hydrodynamic modifications of the plasma in the crossing volume due to the propagation of a third beam. According to 3D simulations and an analytical model, it appears that the long-wavelength expansion-velocity fluctuations produced by the propagation of the third beam in the crossing volume are responsible for this mitigation of energy transfer. This effect could be a cause of the over-estimation of the amount of the transferred energy in indirect-drive inertial confinement fusion experiments. Besides, tuning such long-wavelength fluctuations could be a way to completely inhibit CBET at the laser entrance holes of hohlraums.